Extensive Subcutaneous Abscess in a Patient with Diabetes Mellitus: A Case Report - Tan, Henny Tannady; Wijaya, Jefri; Dharmawan, Ade; Layanto, Nicolas (Yayasan Gema Bina Nusantara, 2025)
Abscess is a collection of pus in a tissue, usually caused by bacterial infection. The main symptoms of abscess are local pain, warmth and oedema (if the abscess is located close to the skin layer) or can be accompanied by constitutional symptoms (if the abscess is far from the skin layer or deep). In this case report, we report a case of extensive subcutaneous abscess in a woman with diabetes mellitus complicated by sepsis. The patient came with complaints of enlarged boils in the abdominal area for 2 weeks ago, this complaint was accompanied by other signs and symptoms of infection. The Infectious Diseases Society of America (IDSA) in 2014 classified SSTI into purulent (furuncles, carbuncles, and abscesses) and non-purulent (cellulitis, erysipelas, and necrotizing infections). There are several predisposing factors for skin abscesses, namely skin trauma, oedema caused by impaired lymphatic flow and venous insufficiency, obesity, immunosuppressive conditions (diabetes, HIV), previous infections (tinea, impetigo, varicella) and previous venous actions. Patients with sepsis syndrome or life-threatening infections need immediate surgical intervention and given combination antibiotics.